Analisis kesesuaian vegetasi di Lapangan Puputan Badung I Gusti Ngurah Made Agung, Denpasar, Bali - Nareswari, I Gusti Ayu Tria; Gunadi, I Gusti Alit; Asmiwyati, I Gusti Agung Ayu Rai (Jurnal Arsitektur Lansekap; Vol.6, No.1, April 2020DO - 10.24843/JAL.2020.v06.i01.p04, 2020)
Lapangan Puputan Badung I Gusti Ngurah Made is a city park in Denpasar that has various functions including as a producer of oxygen, public recreation space for urban communities, and city aesthetics. This study aims to analyze the suitability of vegetation type for city park and analyze the effect of vegetation placement on garden user activities. The method used is observation to obtain data about the type of vegetation and user activities in several areas of the park. The literature study method is used to develop vegetation suitability indicators for city parks and assess the suitability of each vegetation. The results obtained are 64 types of vegetation which are composed of groundcovers, shrubs, and trees. Based on research, as many as 53 types of vegetation are suitable and 11 other types are quite suitable for city parks. The vegetation functions as shade, limiting view, and aesthetics. This function affects user activity in several areas in the park, which limits the view of road users to the park or otherwise, providing a comfortable resting place and facilities throughout the day.